2009
DOI: 10.1021/jp904518e
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into 19-Atom Pd/Pt Nanoparticles: A Computational Perspective

Abstract: We present a systematic study of the structural changes of 19-atom Pd n Pt 19-n nanoparticles as a function of composition, modeling the interatomic interactions with the many-body Gupta potential and using a genetic algorithm to obtain the lowest energy structures for all possible compositions. Topological analysis reveals that most of the structures are based on icosahedral packings and are strongly composition dependent. The pure Pd 19 nanoparticle exhibits a double icosahedral geometry, while the Ino decah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…A more detailed description of different doping at 19 atoms could be found elsewhere. 26,43 Very interestingly and for the first time, we have found that, after a BFGS optimization, a pure platinum nanoparticle of 17 atoms preferentially adopts a cage structure, with an internal cavity of roughly 4.5 A ˚, as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 85%
“…A more detailed description of different doping at 19 atoms could be found elsewhere. 26,43 Very interestingly and for the first time, we have found that, after a BFGS optimization, a pure platinum nanoparticle of 17 atoms preferentially adopts a cage structure, with an internal cavity of roughly 4.5 A ˚, as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 85%
“…34 However, the BLJ model is not representative of metallic bonding, and most works on bimetallic nanoalloys have been restricted to transition metals. [21][22][23][25][26][27][28][29][30][31][32] From a fundamental point of view, it is a good idea to analyze the structural trends in metallic nanoalloys formed by combining two alkali metals. Pure alkali clusters have been instrumental in our present understanding of metal cluster properties, 35,36 and their mixtures might play a similar role in nanoalloy physics.…”
Section: Introductionmentioning
confidence: 99%
“…58 The specific details of the GA we have adopted 56 and the descriptions of previous applications can be found elsewhere. 26,46,59 2.3 The threshold energy method 2.3.1 Description of method. In order to survey the PES of Pd 12 Pt 1 , we have used the threshold method.…”
Section: The Genetic Algorithmmentioning
confidence: 99%